High-Throughput Flow Cytometric Method for the Simultaneous Measurement of CAR-T Cell Characterization and Cytotoxicity against Solid Tumor Cell Lines. (August 2018) - Martinez, Emily M.; Klebanoff, Samuel D.; Secrest, Stephanie; Romain, Gabrielle; Haile, Samuel T.; Emtage, Peter C. R.; Gilbert, Amy E.
High-throughput flow cytometry is an attractive platform for the analysis of adoptive cellular therapies such as chimeric antigen receptor T cell therapy (CAR-T) because it allows for the concurrent measurement of T cell–dependent cellular cytotoxicity (TDCC) and the functional characterization of engineered T cells with respect to percentage of CAR transduction, T cell phenotype, and measurement of T cell function such as activation in a single assay. The use of adherent tumor cell lines can be challenging in these flow-based assays. Here, we present the development of a high-throughput flow-based assay to measure TDCC for a CAR-T construct co-cultured with multiple adherent tumor cell lines. We describe optimal assay conditions (such as adherent cell dissociation techniques to minimize impact on cell viability) that result in robust cytotoxicity assays. In addition, we report on the concurrent use of T cell transduction and activation antibody panels (CD25) that provide further dissection of engineered T cell function. In conclusion, we present the development of a high-throughput flow cytometry method allowing for in vitro interrogation of solid tumor, targeting CAR-T cell–mediated cytotoxicity, CAR transduction, and engineered T cell characterization in a single assay.